The Action of Ayurvedic Formulations and Nitya Virechana on Vitiligo (Shwitra) – A Case Study: Life Sciences-Ayurveda - Topale, Devika; Parwe, Shweta; Nisargandha, Milind; Sawarkar, Punam; Shrivastav, Pooja (International Journal of Life Science and Pharma Research, 2023)
In Ayurveda, skin is described under Kushtha, Charak Samhita explains Shwitra in KushthaChikitsa. Shwitra is found in Charak Samhita, Ashtanghrudaya, Madhavnidan, Bhavprakash, Sharangdhar, and Acharya Sushruta, term it as a Kilas. In the present case, the study patient complains of white-coloured patches with dryness in the affected area. With the help of clinical features, the patient is diagnosed with vitiligo. As per the Ayurvedic treatment principle, both Shodhana and ShamanaChikitsa have been advised to the patient, and without any complication, a significant result has been achieved. Aim of this case is to Achive objectives and study Ayurvedic formulations and Nitya Virechana on Vitiligo . The term Shwitra implies in Sanskrit is Shweta(White), which is present without Kandu and irritation. It is found anywhere on the body; when it presents on the Lips, Buttocks region, it becomes incurable. Vitiligo correlated with Shwitra in Ayurveda. In Vitiligo, there is hypopigmentation occurs. It is described by the eradication of melanocytes present in the basal layer of the epidermis. It is an immune system pathology; thus, treatment likewise stays troublesome; allopathic have only suppressive therapy, not therapeutic, and Ayurvedic medicine has been influential in the beginning phase. In a single case study, a female patient aged 61 yr had white patches on the forehead, hands from the elbow joint, knee joints, and foot area since 2yr. Tridoshaghna, Raktashodhak, Raktaprasadak, and Krimighna drugs are given to patients, which provide a significant result.